2009
DOI: 10.2337/dc09-s203
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in African American Youth

Abstract: OBJECTIVE—To report the prevalence and incidence of type 1 and type 2 diabetes among African American youth and to describe demographic, clinical, and behavioral characteristics.RESEARCH DESIGN AND METHODS—Data from the SEARCH for Diabetes in Youth Study, a population-based, multicenter observational study of youth with clinically diagnosed diabetes aged 0–19 years, were used to estimate the prevalence for calendar year 2001 (692 cases) and incidence based on 748 African American case subjects diagnosed in 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
111
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 167 publications
(121 citation statements)
references
References 54 publications
5
111
1
4
Order By: Relevance
“…This was followed by the Navajo population (USA), American Indians (USA) and African-Americans (USA) (27.7, 23.3 and 19, respectively, per 100,000 person-years) [20,23,44]. The Aboriginal population in Canada also had a high incidence rate (23.3 per 100,000 person-years) [26] (Fig.…”
Section: Study Population and Ethnicitiesmentioning
confidence: 94%
See 2 more Smart Citations
“…This was followed by the Navajo population (USA), American Indians (USA) and African-Americans (USA) (27.7, 23.3 and 19, respectively, per 100,000 person-years) [20,23,44]. The Aboriginal population in Canada also had a high incidence rate (23.3 per 100,000 person-years) [26] (Fig.…”
Section: Study Population and Ethnicitiesmentioning
confidence: 94%
“…The number of children in the populations in which type 2 diabetes was detected ranged from 1,647 [18] to several millions [11][12][13][19][20][21][22][23][24][25] and covered different age categories. The 37 included studies described data about many different ethnicities-Japanese, Taiwanese, multi-ethnic, New Zealand-Maori, New Zealand-European, Turkish, South Asian, Black, Aboriginal, African-American, American Indian, Pima Indian, Ojibwa-Cree, non-Hispanic whites, Hispanic, etc.…”
Section: Study Population and Ethnicitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Diabetic ketoacidosis (DKA) due to insulin deficiency can be a lifethreatening condition, and is often the presenting symptom of new-onset cases in both type 1 and type 2 diabetes. 5 It has been reported to be present in 25% to 30% of type 1 diabetes cases at onset [6][7][8][9][10] and from 4% to 29% in youth with type 2 diabetes, depending on race/ethnicity. [10][11][12][13][14] SEARCH previously reported that the prevalence of DKA at diagnosis was 25.5% in 2002-2003.…”
mentioning
confidence: 99%
“…Em relação à raça das gestantes os dados apresentados também não confirmam os encontrados na literatura, que apontam o aumento dos casos de DM tipo 2 em mulheres de raça não branca [17][18][19] . Em nossa amostra, apesar do ligeiro aumento de casos em gestantes de raça não branca nos últimos anos de estudo em relação aos primeiros, a maioria dos casos corresponderam a gestantes de raça branca.…”
Section: Discussionunclassified